Soil microbial diversity and activity in different climatic zones of Ukraine - О. S. Demyanyuk; L. Y. Symochko; I. I. Mostoviak (Regulatory Mechanisms in Biosystems, 2020)
Soils are dynamic biological matrices featuring a complex microbiome that has an integral role in all ecosystem processes. At the system level, microbial communities regulate ecosystem functioning and modulate resistance and resilience to anthropogenic impact. Ecological status of soils depends on the structure and activity of soil microbiome. The aim of this study was long-term investigations of soil microbiome in different climatic zones of Ukraine, namely the structure and diversity of microbial communities, direction of soil microbiological processes in natural and transformed ecosystems. Four types of soil were studied in different natural and climatic zones: Steppe zone – Donetsk region, Forest-steppe – Vinnytsia region, Polissya – Chernihiv region, Carpathian region. Microbiological studies of soil were carried out according to generally accepted methods in soil microbiology. Diversity of soil microbiome was estimated using Shannon and Simpson indices. The direction of microbiological processes in the soil was determined by the appropriate coefficients: mineralization, oligotrophy, pedotrophity, and transformation of organic matter. The results of soil monitoring in various natural and climatic zones of Ukraine showed a correlation between the agroecological conditions and activity of microbiocenosis. The soil of natural ecosystems was characterized by a high total number of the microorganisms with a balanced structure of various ecological-trophic groups and balanced mineralization-immobilization processes, organic matter decomposition, and humus accumulation. The chernozem soil was characterized by more stable and balanced structure of microbiocenosis than soddy-podzolic, brown and grey forest soils. The growth of the proportion of micellar organisms occurs during the long-term application of mineral fertilizers. Data of functional communities and functional processes helped estimate specific microbial responses to anthropogenic impact. The most significant influence of agricultural activity on the soil microbiota was observed in the poorly soddy-podzolic, brown and grey forest soils, where the cultivation of the crops without fertilization resulted in a decrease of the total number of microorganisms by 2.2–4.5 times. Soil microbial diversity was practically twice lower in these ecosystems in comparison with the natural ones. Soils with low content of organic matter and acidic medium: soddy-podzolic, brown forest and grey forest soils have been characterized by a high number of micromycetes and a relatively low number of eutrophic and nitrogen-fixing microorganisms. This article summarizes important results of long term investigations of soil microbiome: structure, interaction, functioning, activity and diversity in the main types of soils on the territory of Ukraine.